A study on anxiety in music performance among music students / Zulhairi Abdul Jalil - Abdul Jalil, Zulhairi (2013)
The purpose of this study is to investigate the anxiety in music performance among music student of Faculty of Music, UiTM. This study was conducted according to the specification of quantitative research, in which it has been conducted among forum class students of Bachelor of Music Performance, faculty of music, UiTM Shah Alam. The objective of this study is to find causes and effects of anxiety in performance among music students in Faculty of Music, UiTM Shah Alam. Besides, there are also to investigate the different level of situation that causes the anxiety in music performance. A survey questionnaire was hand out to 30 students who were taking forum classes. The results of this study show that the students have their own different perception of their situation of anxiety that causes different effect in their performances. The result brings to the reason of why forum class's students refuse to do their turn earlier than the outline dated that had been informed. Other than that, the result indicate that the student were not able to control their anxiety in performance.